2022
DOI: 10.2337/dc22-0549
|View full text |Cite
|
Sign up to set email alerts
|

Does the Effect of a 3-Year Lifestyle Intervention on Body Weight and Cardiometabolic Health Differ by Prediabetes Metabolic Phenotype? A Post Hoc Analysis of the PREVIEW Study

Abstract: OBJECTIVE To examine whether the effect of a 3-year lifestyle intervention on body weight and cardiometabolic risk factors differs by prediabetes metabolic phenotype. RESEARCH DESIGN AND METHODS This post hoc analysis of the multicenter, randomized trial, PREVention of diabetes through lifestyle interventions and population studies In Europe and around the World (PREVIEW), included 1,510 participants with prediabetes (BMI ≥25… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Indeed, dietary interventions have a differential effect on body weight, weight maintenance and cardiometabolic risk factors in men compared to women, as extensively reviewed elsewhere [ 23 ]. The recent PREVIEW study investigated age- and sex-specific effects of a low-energy diet (LED), followed by a 3 year lifestyle-based weight maintenance intervention in overweight adults with prediabetes [ 83 ]. A lifestyle intervention had less beneficial effects with respect to body composition and cardiometabolic health markers in older than younger adults, despite better weight maintenance, which might be due to the loss of more fat-free mass in older adults.…”
Section: Lifestyle Interventions To Improve Cardiometabolic Health An...mentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, dietary interventions have a differential effect on body weight, weight maintenance and cardiometabolic risk factors in men compared to women, as extensively reviewed elsewhere [ 23 ]. The recent PREVIEW study investigated age- and sex-specific effects of a low-energy diet (LED), followed by a 3 year lifestyle-based weight maintenance intervention in overweight adults with prediabetes [ 83 ]. A lifestyle intervention had less beneficial effects with respect to body composition and cardiometabolic health markers in older than younger adults, despite better weight maintenance, which might be due to the loss of more fat-free mass in older adults.…”
Section: Lifestyle Interventions To Improve Cardiometabolic Health An...mentioning
confidence: 99%
“…A lifestyle intervention had less beneficial effects with respect to body composition and cardiometabolic health markers in older than younger adults, despite better weight maintenance, which might be due to the loss of more fat-free mass in older adults. The LED, followed by a lifestyle intervention, showed less beneficial effects on body weight and body composition in women than men [ 83 ]. The available evidence suggests that factors such as age and sex should be taken into account to optimize prevention and treatment strategies for those at risk of or already living with cardiometabolic diseases.…”
Section: Lifestyle Interventions To Improve Cardiometabolic Health An...mentioning
confidence: 99%
See 1 more Smart Citation
“…Patients diagnosed with pre-diabetes are at higher risk of developing T2DM (16), and macrovascular complications may happen well before official diagnosis of diabetes (17). Management of lifestyle, weight, blood sugar, and blood lipids is essential for preventing the incidence of adverse events (18)(19)(20)(21)(22)(23). On the aspect of blood lipids, individuals who are under condition of pre-diabetes tend to have higher prevalence of dyslipidemia than people whose plasma glucose are in the normal range; also, research has shown a positive association between high level of LDL-C and increased probability of pre-diabetes (24, 25).…”
Section: Introductionmentioning
confidence: 99%
“…However, the efficacy of LCDs has been examined scarcely in individuals with i-IFG, who share the same pathophysiological defects as those in people with type 2 diabetes (2). One of the first pieces of evidence comes from a post hoc analysis of the PREVIEW (Prevention of Diabetes Through Lifestyle Interventions and Population Studies in Europe and Around the World) study (5). PREVIEW was conducted among 869 overweight (BMI $25 kg/m 2 ) individuals (aged 25-70 years) with i-IFG.…”
mentioning
confidence: 99%